Analisis Pengaruh Person-Organization Fit dan Person-Job fit terhadap Kinerja Karyawan - Utami Tunjung Sari; Niken Permata Sari; Sinta Manggala (Management Insight: Jurnal Ilmiah Manajemen, 2025)
Person-Organization fit has provided a deep understanding of increasing the fit between employees and the organization, retaining employees in the long term by increasing employee satisfaction and commitment to the company, as well as improving individual outcomes which have implications for sustainable strategic growth for an organization. Individual-job fit (person-job fit) is a job specification process as an effort to help identify individual employee competencies needed to obtain success, such as knowledge, abilities, skills and other factors that can refer to obtaining superior performance, therefore variables This is very important for the company to pay attention to. This study aims to analyze the effect of person-organization fit and person-job fit on employee performance in companies in Yogyakarta. The sample in this study are employees who work for organizations/companies in the Special Region of Yogyakarta. This study uses primary data. The sampling technique in this study used purposive sampling. A total of 93 respondents participated in this study. The data collection tool used in this study was a questionnaire distributed online. The data in this study were processed using SPSS with multiple linear regression analysis methods. The results of this study indicate that there is a significant positive effect of person-organization fit and person-job fit on employee performance. Keywords: Person-Organization Fit, Person-Job Fit, Employee Performance